2001
DOI: 10.1128/jb.183.19.5632-5638.2001
|View full text |Cite
|
Sign up to set email alerts
|

Rhamnose Biosynthesis Pathway Supplies Precursors for Primary and Secondary Metabolism in Saccharopolyspora spinosa

Abstract: Rhamnose is an essential component of the insect control agent spinosad. However, the genes coding for the four enzymes involved in rhamnose biosynthesis in Saccharopolyspora spinosa are located in three different regions of the genome, all unlinked to the cluster of other genes that are required for spinosyn biosynthesis. Disruption of any of the rhamnose genes resulted in mutants with highly fragmented mycelia that could survive only in media supplemented with an osmotic stabilizer. It appears that this sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 16 publications
2
59
0
2
Order By: Relevance
“…Rhamnose biosynthesis has been delineated in M. tuberculosis and M. smegmatis and genes encoding the key enzymes have been characterized in M. tuberculosis (Cole et al, 1998 ;Ma et al, 1997). Unlike the situation in enteric bacteria the mycobacterial genes for rhamnose biosynthesis are dispersed around the chromosome in a similar fashion to that described in Saccharopolyspora spinosa (Madduri et al, 2001). Rhamnose is also required for glycosylation of GPLs in M. smegmatis, and genes for glucose-1-phosphate thymidylyltransferase (rmlA) and dTDP glucose 4,6-dehydrogenase (rmlB) occur in the GPL biosynthetic locus.…”
Section: Discussionmentioning
confidence: 88%
“…Rhamnose biosynthesis has been delineated in M. tuberculosis and M. smegmatis and genes encoding the key enzymes have been characterized in M. tuberculosis (Cole et al, 1998 ;Ma et al, 1997). Unlike the situation in enteric bacteria the mycobacterial genes for rhamnose biosynthesis are dispersed around the chromosome in a similar fashion to that described in Saccharopolyspora spinosa (Madduri et al, 2001). Rhamnose is also required for glycosylation of GPLs in M. smegmatis, and genes for glucose-1-phosphate thymidylyltransferase (rmlA) and dTDP glucose 4,6-dehydrogenase (rmlB) occur in the GPL biosynthetic locus.…”
Section: Discussionmentioning
confidence: 88%
“…The next step after deoxygenation is reduction of the 3-keto group of the pathway intermediate. SpnQ is believed to serve this role in the biosynthesis of the forosamine component of spinosad (23). A homolog of SpnQ was not found within the Ͼ80-kb sequenced segment from the chalcomycin producer.…”
Section: Resultsmentioning
confidence: 98%
“…The tetracyclic aglycone scaffold is delicately constructed first by type I polyketide (PK-I) 2 synthases, followed by proposed postmodification events, including FAD-oxidation at C-15, Michael addition between C-3 and C-14, ␥-dehydration at C-11, and Diels-Alder cyclization (4,5). The spinosyn biosynthesis genes recently cloned and sequenced are located in an ϳ80-kb cluster of the S. spinosa genome, except that the four genes involved in L-rhamnose (L-Rha) biosynthesis, gtt (NDP-glucose synthase), gdh (NDP-glucose 4,6-dehydratase), epi (NDP-4-keto-6-deoxyglucose epimerase), and kre (NDP-4-ketorhamnose reductase), are located in three different regions of the genome (6). Previous genetic experiments have suggested that the polyketide aglycone is biosynthesized prior to immediate attachment of L-Rha by the rhamnosyltransferase SpnG, followed by consecutive tri-O-methylation of the L-Rha on resulting spinosyn rhamnosyl pseudoaglycone (SRPG) and then by the addition of D-forosamine to give spinosyns (Scheme 1) (4, 7).…”
mentioning
confidence: 99%